Abordagem metabolômica baseada em RMN para estudo de cascas e folhas do Banco Ativo de Germoplasma de Spondias mombin - Silva, Gladyane Santos da (2021)
The exploitation of fruit trees in the Northeast region of Brazil occurs in the great majority, in an extractive manner, using inadequate management techniques that lead to the loss of genetic resources and genotypes containing bioactive compounds of pharmacological importance. This practice is repeated with the cajazeira tree, whose cultivations in domestic and commercial orchards are few. As it is a species still in domestication, cytogenetically little known, and with high productive potential in the regions of origin, it is hugely significant to establish strategies for conserving its genetic variability in order to avoid the risk of genetic erosion and maintain it available for use in plant breeding programs. Thus, in the present work, a chemical profile study of the active germplasm bank (AGB) was carried out containing 22 accessions of cajazeira (separated between leaves and barks) divided between clones and progenies. To contribute to generating knowledge and adding value to the AGB, the non-target metabolomics technique was applied through an approach based on Nuclear Magnetic Resonance to elucidate the accessions and genotypes' chemical profiles. It was observed the presence of metabolites of chemical/pharmacological interest with possible technical, medicinal, and nutritional applications, among which quercetin, ellagic acid, and gallic acid can be mentioned. Sugar molecules and amino acids already reported as markers of resistance to stress conditions were also found in abundance in the leaves and bark. Multivariate analysis was used to investigate the chemical variability between accessions and correlate the described metabolites with the place and time of collection. Thus, the results obtained justified the establishment of a chemical base associated with the active germplasm bank, which can be useful to subsidize programs of genetic improvement of the cajazeira tree, essential to increase the agricultural productivity and nutritional quality of the crops in the face of adverse conditions to which they are subjected.